Effectiveness of Enterprise Development Tool Promoted by the Ministry of Industry: Outcome from Field Survey - Neupane, Rabindra; Basnet, Bhupindra Jung; Neupane, Ashutosh (Nepal Journal of Multidisciplinary Research, 2025)
Background: The objective of this study is to analyze the effect of enterprise development tool called Business Development Services (BDS) designed and promoted by the Ministry of Industry for creation and development of micro-enterprises in Nepal. The tool is composed of different components supporting micro-enterprise creation and growth. This research is based on the primary data collected from the field survey of micro-entrepreneurs of Banepa Municipality and Chauri Deurali Village Palika of Kavre District. Kavre district is nearby Kathmandu and easy to reach by road transport. The Ministry of Industry has implemented BDS program in this district from the year 2007 so that BDS suppliers and entrepreneur associations have generated sufficient experience and information on the implemented modality. Objective: The general objective of this research is to analyze the effectiveness of BDS, a tool for micro-enterprise development. Specifically, this research is aimed on analyzing surveyed data of micro-entrepreneurs for the assessment of the effectiveness of provided BDS supports to them for the development of their enterprises. Methods A quantitative approach has been used in this research. For the survey purpose, micro-entrepreneurs are randomly sampled from the population of total created enterprises at the sample areas. The sample areas are purposively selected due to their richness in information holdings, number of created micro-enterprises, and experience in delivering BDS. Questionnaires to collect opinion on the effectiveness of the delivered BDS is structured using five point Likert scale. Both descriptive and inferential statistical analysis are applied to analyze the surveyed data. Findings: Both the descriptive and inferential analyses have depicted that that all components of BDS are significantly effective for the development of micro-enterprises. Conclusion: The designed BDS package is very useful to micro-entrepreneurs for the creation and growth of their enterprise. The applied holistic mechanism in the design and interventions of the BDS have helped to enhance its effectiveness as expected by the promoting agency. Novelty: The dearth of research in this subject in Nepal make it a novel topic. Although, the effectiveness of BDS as a tool of micro-enterprise development is evaluated several times under the funded project work of the Ministry of Industry whereas the academic research in this topic is rear in Nepal.